ENGLISH PHRASES USED IN ACADEMIC WRITING - Feruza Kucharova Alisher kizi; Usmonova Sabrina Siroj kizi (TADQIQOTLAR, 2025)
Abstract: English phrases play a vital role in academic writing, serving as essential tools to structure arguments, present evidence, and articulate ideas clearly and persuasively. These phrases often include connectors, transitions, and signposting language that guide readers through the text. Academic writers use them to express cause and effect, compare and contrast, and highlight significance, among other functions. Examples include "it is widely acknowledged that," "in contrast to," "the findings suggest that," and "a possible explanation for this is." Mastery of these phrases enhances the coherence and professionalism of academic work, making arguments more accessible to a global audience. Additionally, they allow for nuanced expression and adherence to academic conventions, which are critical for effective communication in scholarly contexts.